Inventory Control Analysis Hospital Bed Manual Unit PI-108MS, PI-208MS, PI-308MS Forecasting and Economic Order Quantity (EOQ) At PT. XYZ - Yusita Attaqwa; Jihan Pradesi; Arina Fardiana (International Journal of Computer and Information System (IJCIS), 2021)
Raw material inventory control is a series of things to determine the level of inventory, the time of purchase and the amount of inventory that must be provided. The Economic Order Quantity (EOQ) method is one of the inventory management techniques by considering storage costs and ordering costs. The value is generated by the term reorder point. This value is used to place orders that the company needs to place. 44 units, 68 units, and 36 units are the quantities needed by PT XYZ in every order. So PT XYZ had to do 46 times, 73 times, and 27 unit orders to fulfill their needs.